Leading from the top or leading from within? A comparison between coaches` and athletes` leadership as predictors of team identification, team confidence, and team cohesion - Fransen, K.; Decroos, S.; Vande Broek, G.; Boen, F. (International Journal of Sports Science & Coaching, 2016)
The present study used a sample of team sport athletes (N?=?343) to investigate to what extent the leadership quality of the coach and the athlete leaders was related to athletes` team confidence and team cohesion. The findings demonstrated that the leadership quality of both coaches and athlete leaders predicted a unique part of the variance of team confidence and team cohesion. In addition, members` identification with the team was demonstrated to be an important mechanism underlying this relation, thereby supporting the Social Identity Approach to Leadership. We conclude that both coaches and athlete leaders can inspire players to identify with their team. In turn, this feeling of `us`, rather than being a group of I`s, predicts a stronger confidence in obtaining team goals and fosters the task and social cohesion within the team. When coaches share the lead with their athletes, an optimal team environment can be created. ABSTRACT FROM AUTHOR